Advancing U.S.-Australian combined amphibious capabilities - Leed, Maren (Center for Strategic & International Studies (CSIS) Rowman & Littlefield, 2015)
The study examines the demand for amphibious capabilities in the Indo-Asia-Pacific region and explores the strategic and operational utility of various models for combined U.S. and Australian amphibious forces